PENERAPAN TEKNIK PUBLIC SPEAKING UNTUK MENGATASI DISLEKSIA RINGAN HURUF B-D DAN AKHIRAN -NG PADA SISWA SEKOLAH DASAR - Hasanah, Mutiatul; Jannah, Ummi Aisyatus Salehah Ahlul (CV. Jendela Gagasan, 2024)
Fluent reading skills are a crucial foundation for children's academic success. However, many early-grade students struggle with specific difficulties, such as distinguishing similar letters (e.g., B and D) and pronouncing word endings like -ng. This study aims to examine the effectiveness of public speaking techniques in improving reading skills in young children facing such challenges. This case study involved a first-grade student with reading difficulties. A structured and repetitive public speaking intervention was implemented at home. Data were collected through direct observation, reading ability assessments, and parental feedback over several weeks. The results showed a significant improvement in the student's ability to differentiate between B and D and in pronouncing words ending in -ng. The child also demonstrated increased confidence and fluency when reading aloud, both in private and in front of others. Statistical analysis indicated a meaningful impact of the intervention on reading accuracy and speaking confidence. In conclusion, public speaking techniques are effective in supporting early literacy development by enhancing articulation and self-confidence. This study highlights the vital role of family and community involvement in helping children overcome reading challenges.